2007
DOI: 10.3171/spi.2007.6.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage total C-2 intralesional spondylectomy for chordoma with three-column reconstruction

Abstract: ✓Chordomas are locally invasive, malignant bone tumors that rarely occur in the cervical spine. En bloc resection or even fully resecting the tumor along its margin offers improved patient survival and a potential disease cure. Complete resection of tumors involving the upper cervical vertebrae requires a combined anterior–posterior approach but is complicated by the presence of vertebral arteries (VAs). In addition, reconstruction of the postresection defect may be prone to failure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 17 publications
0
22
0
3
Order By: Relevance
“…Since Goel et al [10] first reported a case of transoral plate and screw fixation of the clivus to the body of the cervical vertebra, several studies have been published using the clival screw fixation for the craniovertebral region [8,9]. However, the anatomy of the clivus and the geometry of the craniocervical junction present challenges for the placement of instrumentation, and also there are no literature that have document the entry point, trajectory, and optimal length of clival screws; our next logical step was to study the anatomic of clival screw fixation for the craniovertebral region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Goel et al [10] first reported a case of transoral plate and screw fixation of the clivus to the body of the cervical vertebra, several studies have been published using the clival screw fixation for the craniovertebral region [8,9]. However, the anatomy of the clivus and the geometry of the craniocervical junction present challenges for the placement of instrumentation, and also there are no literature that have document the entry point, trajectory, and optimal length of clival screws; our next logical step was to study the anatomic of clival screw fixation for the craniovertebral region.…”
Section: Discussionmentioning
confidence: 99%
“…Suchomel et al [8] created a small rightsided submandibular channel through the floor of the mouth at vertical angle via an oral surgical route for anticipated clival screws. Rawins et al [9] gained access to the anterior upper cervical spine and expose clivus through a mandibular osteotomy and soft palate split.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Despite the recognition that en bloc resection was ideal, cervical chordomas, particularly if located in the C1-2 segments, have largely been managed via intralesional resection, as with clival lesions. 2,12,31,32 Advancement in surgical techniques and reconstruction has permitted more of these neoplasms to be removed en bloc. 1,13,18,21,27,29,32 With the exception of a series of 5 cases published by Hsieh et al, 20 who demonstrated that wide or marginal en bloc chordoma excision was optimal for prolonging disease-free survival, the majority of literature addressing en bloc removal of cervical chordomas has been limited to reports of 3 cases or fewer.…”
mentioning
confidence: 99%
“…27 Following en bloc chordoma resection resulting in 3-column disruption, the authors reconstructed the anterior column with a mesh cage spanning the clivus to C-3, and lateral mass cages spanning C-1 to C-3 and C-1 to C-4, supplemented with posterior instrumentation for tension banding. The authors felt that this construct would increase "surface area of potential bone fusion" and "offload the strain on the posterior occipitocervical fixation."…”
Section: Discussionmentioning
confidence: 99%